2021
DOI: 10.1002/acr2.11216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Beliefs and Preferences for Reducing Sedentary Behavior Among Adults With Symptomatic Knee Osteoarthritis or Knee Replacement

Abstract: Objective Physical activity has numerous benefits for those with symptomatic knee osteoarthritis (KOA) or knee replacement, yet many individuals engage in insufficient activity. The purpose of this study was to explore beliefs about sedentary behavior, barriers to standing, and program preferences for adults with symptomatic KOA or knee replacement. Methods Forty‐two individuals ≥50 years with symptomatic KOA or knee replacement completed an online survey assessing current knee pain and function, sitting time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…3 ). A duration of 30 min of continuous sedentary time was chosen based on participant preferences on the frequency of interrupting sedentary behavior [ 40 ]. When the app detects movement of a predefined magnitude and threshold (e.g., using the phone while seated would be below the threshold, whereas walking with the phone would be above the threshold), the 30-min timer will restart; thus, the app will only provide notifications when prolonged bouts of minimal to no movement are objectively detected of a different message.…”
Section: Methodsmentioning
confidence: 99%
“…3 ). A duration of 30 min of continuous sedentary time was chosen based on participant preferences on the frequency of interrupting sedentary behavior [ 40 ]. When the app detects movement of a predefined magnitude and threshold (e.g., using the phone while seated would be below the threshold, whereas walking with the phone would be above the threshold), the 30-min timer will restart; thus, the app will only provide notifications when prolonged bouts of minimal to no movement are objectively detected of a different message.…”
Section: Methodsmentioning
confidence: 99%
“…38 With the widespread availability of consumer-grade wearable monitors, including fitness trackers, step counting is another popular and relatively accurate way to measure PA, both among patients and researchers. 17 Measuring steps allows for the inclusion of a wide range of daily activities (eg, chores, grocery shopping) and may motivate adults to reduce sedentary behaviors, 39,40 which are associated with increased risk of cardiovascular disease and all-cause mortality. 17 White et al found that 6000 steps per day was the threshold for determining whether patients with knee OA would or would not develop functional limitations.…”
Section: Physical Activitymentioning
confidence: 99%
“…Some quantitative studies abroad have focused on the comparison between SB and physical activity (PA) in preoperative and postoperative TKA patients [4,8] . A few studies used accelerometers to objectively measure SB in post-TKA patients, and the results showed that numerous factors affect SB in post-TKA patients, mainly age [9] , body mass index (BMI) [10] , gender [9] , occupation [11] , education level [12] , already having a sedentary lifestyle [10,13] , and one's psychological state [13] before the operation, but the factors in uencing of sedentary behaviours in elderly postoperative TKA patients remain unclear. In addition, most of the existing studies on the in uencing factors of SB lack a theoretical framework, and the analysis results are scattered.…”
Section: Introductionmentioning
confidence: 99%